Classroom Membership: What Does That Mean Exactly? - Heath, Katie (Journal of the American Academy of Special Education Professionals, 2021)
Classroom membership is essential in today’s classrooms as students need to feel safe and secure in their participatory roles. Allowing a student’s voice is essential in allowing them the opportunity to communicate with their peers. In this study, the author looked at how the use or non-use of the iPad (as a form of assistive technology) affected membership of students with disabilities. Findings showed that iPad integration played a vital role in increasing or decreasing participation through communication and the feelings of membership in the classroom. Ultimately, how the teacher plans and prepares for the integration of the iPad into the classroom ultimately affects the membership opportunities for students with disabilities. Included are the stories of four students and their use of the iPad.